2023
DOI: 10.3390/microorganisms11102500
|View full text |Cite
|
Sign up to set email alerts
|

LRRC25 Inhibits IFN-γ Secretion by Microglia to Negatively Regulate Anti-Tuberculosis Immunity in Mice

Gang Sheng,
Hongqian Chu,
Huijuan Duan
et al.

Abstract: Background: Leucine-rich repeat-containing protein-25 (LRRC25) can degrade the ISG15 gene in virus-infected cells and prevent overactivation of the type Ⅰ IFN pathway. However, the role of LRRC25 in bacterial infection is still unclear. In this pursuit, the present study aimed to explore the regulatory role and mechanism of LRRC25 in microglia infected with Mycobacterium tuberculosis in a mouse model. Methods: Q-PCR, WB, and cell immunofluorescence were employed to observe the change in LRRC25 in BV2 cells inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In recent years neuroinflammation has emerged as a third hallmark feature of AD ( Leng and Edison, 2021 ; Zhou et al, 2021 ; Mangalmurti and Lukens, 2022 ). LRRC25’s role in neuroinflammation in AD is also intriguing given that LRRC25 overexpression impairs and LRRC25 knockout potentiates NF-κB activation thereby increasing the production of inflammatory cytokines ( Feng et al, 2017 ), More recently LRRC25 has also been shown to inhibit IFN-γ secretion by microglia ( Sheng et al, 2023 ). It is important to note that the anti-inflammatory role of LRRC25 has been demonstrated in response to viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years neuroinflammation has emerged as a third hallmark feature of AD ( Leng and Edison, 2021 ; Zhou et al, 2021 ; Mangalmurti and Lukens, 2022 ). LRRC25’s role in neuroinflammation in AD is also intriguing given that LRRC25 overexpression impairs and LRRC25 knockout potentiates NF-κB activation thereby increasing the production of inflammatory cytokines ( Feng et al, 2017 ), More recently LRRC25 has also been shown to inhibit IFN-γ secretion by microglia ( Sheng et al, 2023 ). It is important to note that the anti-inflammatory role of LRRC25 has been demonstrated in response to viral infections.…”
Section: Discussionmentioning
confidence: 99%